Embassy of Nature. The importance of overgrowth and other relationships with plants - KOWALEWSKI, MACIEJ; Ostrowski, Marek; Sobolewska, Marta; Kowalewska, Dorota; Predel, Natalia; K, (Porównania, 2024)
Human–plant interactions are dominated by practices of control, maintenance of order and demarcation of interspecies contact zones. Activities that fall within this paradigm (such as lawn trimming, weed removal, and algae control) are "transparent” activities, more or less unreflective. Although we know more and more about water retention, the role of urban meadows and biodiversity, refraining from mowing grass in public spaces is still met with accusations of “neglecting the property”. In our work, we refer to several concepts, including the idea of consent to overgrowth put forward by Ariel Modrzyk (2022). Seeking to break the dominant paradigm of control, we discuss the physical and symbolic meaning of overgrowth, referring to the spontaneous and unregulated proliferation of plant species in urban areas, often occurring in abandoned spaces. We are conducting the research work as a part of the “Laboratorium badań nad szczęściem. Po komfortocenie” project, implemented by the Goethe-Institut, The Bęc Zmiana Foundation and the Center for Art and Urbanistics (ZK/U) in Berlin. In the text, we present the artistic action of establishing the Ambasada Natury (Embassy of Nature), undertaken by a local coalition of artists in 2023. As part of this action, we placed boxes in selected habitats around the city, which allowed vegetation to grow through self-seeding without human intervention. We describe the concept of Ambasada Natury as a gesture to establish a diplomatic relationship with flora from outside the city boundaries, focusing around a vision of future with sustainable cities and the extent to which we can accommodate plant growth in a built-up environment.